Mathematical characteristics of the airflow through vents in porous exterior building shading board. Issue 9 (20th October 2020) - Li, Du; Lin, Ping; Chen, Yongming
ABSTRACT: The shading board has a negative influence on window ventilation while it is blocking direct sunlight. Circle vents are designed in the shading board to decrease the negative ventilation effect because air can flow through vents to compensate for the obstruction effect of shading board in this study. The thickness and the diameter of vents are calculated precisely and the optimum size is obtained. Mathematical analysis and ANSYS simulation analysis of the micro ventilation in vents are performed at the same time. From the comparison and validation of this analysis, the relationship beyond air velocity, shading board thickness and vent diameter is concluded to supply reliable basis and good reference for shading design and window ventilation analysis in the building.